Allegorical figure holding a palm tree - Ghosh, Ayan (Jio Institute, 2023)
Over 150 years of its existence, the Flora Fountain had deteriorated due to exposure to the elements and the pollution caused from vehicular emissions due to its location at a busy traffic intersection. Not only had the Portland stone turned dark, but the fountain was leaking. Major restoration work was undertaken in 2017 by BMC and INTACH under the supervision of architect Vikas Dilawari.